Juvenile curfew and crime reduction: Evidence from Brazil. Issue 2 (25th September 2020) - Carazza, Luís; da Mota Silveira Neto, Raul; Emanuel, Lucas
Abstract: The city of Fernandópolis, located in the countryside of the state of São Paulo, Brazil, imposed a juvenile curfew in 2005. This decision was not made at the municipal or state level, but in a courtroom. Subsequently, other municipalities in the state of São Paulo decided to adopt a juvenile curfew. To assess the effect of the curfew on reducing crime, this paper uses the difference‐in‐differences estimation to compare its impact, relative to municipalities that did not adopt a curfew. The results suggest that the curfew led to a decrease of 17.9% in thieves per thousand inhabitants in municipalities that adopted it. Resumen: La ciudad de Fernandópolis, situada en el interior del estado de São Paulo (Brasil), impuso un toque de queda para los jóvenes en 2005. Esta decisión no se tomó a nivel municipal o estatal, sino en un tribunal. Posteriormente, otros municipios del estado de São Paulo decidieron adoptar un toque de queda juvenil. Para evaluar el efecto del toque de queda en la reducción de la delincuencia, en el presente artículo se utiliza la estimación de las diferencias en diferencias para comparar su impacto, con respecto a los municipios que no adoptaron un toque de queda. Los resultados sugieren que el toque de queda provocó una disminución del 17, 9% del número de ladrones por cada mil habitantes en los municipios que lo adoptaron. 抄録: ブラジルのサンパウロ州の田舎に位置するフェルナンドポリス市は、2005年に未成年の夜間外出禁止令を出した。これは市や州レベルではなく法廷で決定されたものである。その後、サンパウロ州の他の自治体も未成年の夜間外出禁止令を採択した。本稿では、差分の差分法による推定を行い、夜間外出禁止令が犯罪の低減に及ぼす影響を、夜間外出禁止令を採用しなかった自治体と比較して評価した。その結果、夜間外出禁止令を施行した市町村では、住民千人当たり17.9%の盗難が減少した。